Moral Support: How Moral Values Shape Foreign Policy Attitudes. (4th June 2014) - Kertzer, Joshua D.; Powers, Kathleen E.; Rathbun, Brian C.; Iyer, Ravi
Abstract : Although classical international relations theorists largely agreed that public opinion about foreign policy is shaped by moral sentiments, public opinion scholars have yet to explore the content of these moral values, and American IR theorists have tended to exclusively associate morality with liberal idealism. Integrating the study of American foreign policy attitudes with Moral Foundations Theory from social psychology, we present original survey data showing that the five established moral values in psychology—harm/care, fairness/reciprocity, authority/respect, ingroup/loyalty, and purity/sanctity—are strongly and systematically associated with foreign policy attitudes. The "individualizing" foundations of harm/care and fairness/reciprocity are particularly important drivers of cooperative internationalism and the "binding" foundations of authority/respect, ingroup/loyalty, and purity/sanctity of militant internationalism. Hawks and hardliners have morals too, just a different set of moral values than the Enlightenment ones emphasized by liberal idealists.